(untitled) (Clío & Asociados. La historia enseñada. ISSN: 2362-3063, 2021)
Taking into account the changes that the subject has undergone within the national curriculum, also the reduction of schedules and elimination in the last two years of secondary education, the purpose of this article is to identify, from the study programs of the subject, the curricular orientations on the formative contribution of history teaching in schools. It’s framed in the analysis of the disciplinary code proposed by Cuesta Fernández. Currently, the subject has been called into question with respect to its usefulness and contribution to student learning, to this end, teaching requires concrete actions in order to improve the quality of disciplinary learning, for this reason, the content analysis of official state documents must necessarily be interpreted under the lens of contemporary competencies, this revalues the discipline and the work of the teacher as an expert in education.